PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN IPS SD - Anna Maria Oktaviani; Arita Marini; Fitriyani Fitriyani (Jurnal Holistika, 2022)
The importance of character education is applied in the learning process. The implementation of character education in the learning process for inculcating student character values can be instilled or developed through Social Sciences (IPS) subjects. Social studies learning process takes place with a contextual approach. The purpose of this study is to determine character education through elementary social studies learning. The method used is literature study. The results of the study are that the cultivation of student character education can be instilled or developed through Social Sciences (IPS) subjects. The application of character education, of course, goes through various stages in the ongoing social studies learning.